Effect of Cryopreservation Factors on the Energetic Metabolism of Cyprinus carpio L. activated Spermatozoa - Cherepanov, V. V. (Problems of Cryobiology and Cryomedicine, 2003)
We have investigated the cryopreservation factors (hypothermia, hypertonia, freezing and thawing) on the content of such key energetic metabolites as glucose-6-phosphate (G6P), pyruvate (PV), lactate and main macroergic phosphates of ATP and creatinephosphate (CP) in Cyprinus carpioL. spermatozoa to reveal the most cryosensitive metabolic reactions. It has been established that all the factors studied cause significant alterations in an energy metabolism of the majority of cells; the methods for fish sperm cryopreservation used do not provide a complete integrity of internal functional parameters for all the cells.